Fraud Prevention of Village Fund Management - Erna Hendrawati; Mira Pramudianti; Khoirul Abidin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Fraud Prevention refers to any effort or action done to reduce opportunities for fraud, as well as to prevent and evaluate any conduct that poses a risk of fraud. The goal of this research is to see how village officials' competency, internal control systems, individual morality, and whistleblowing affect fraud prevention in village fund administration. This study focused on the village government in Menganti sub-district, Gresik regency, Surabaya, which received village funding. The village chief, secretary, and treasurer were the participants in this study. 66 respondents are selected for the sample using the saturation sampling technique. Spreading questionnaire was used to collect data, and the model used was SEM-PLS (Partial Least Square) using WarpPLS. The results of the study on village officials' competence, morality, and whistleblowing have an impact on fraud prevention, while the internal control system has no impact.